Draft Annual Plan 1986-87 Volume : VII Government of Assam - Planning Commission (Planning Commission, 1986)
The Assam Agricultural University Complex located at Diphu (Karbi Anglong) has been undertaking Research work in different developmental aspects on local-varieties of cereals, pulses and adaptibility of H.Y.V. crops in different conditions of the hill areas.
Government of Assam